Cultural Beliefs And Practices In New Born Care In Rural Villages Of North Karnataka (Journal of Pharmaceutical Negative Results, 2022)
A mother and her baby's health depend on prenatal and postnatal care. India has 27 million births annually. About four million Indian babies die in their first month of birth. Mortality may be affected by home-based cultural practises and beliefs. The study aimed to find the cultural belief and practices on new born care in the rural villages.The study was conducted in the rural villages of Belgaum District. A total of 60 mothers who had children of 0-1 years were included in the study and data was collected for cultural and new born practices using the interview technique. The data was analysed using the inferential statistics and descriptive statistics. Coconut oil massage before the birth was applied by 98.05% of the mothers, 96% of mothers used baby powder and 96 % of mothers used loban (benzoin resin) After the bath and all 60 mothers applied kajal on the eyes and face of baby for preventing the bad eyesight’s.The study concluded that majority of the mothers have belief in the cultural and practice the traditional methods in the care of the new born.